Effect of remediation of polychlorinated biphenyls (PCBs) contaminated soil by combined treatment of nanoscale zero-valent iron and PCBs-degrading strain - SHAO Lyuyang; CHEN Xi; SHEN Chaofeng (浙江大学学报. 农业与生命科学版)
Polychlorinated biphenyls (PCBs) are typical pollutants in soil. Nanoscale zero-valent iron (nZVI) can effectively dechlorinate high-chlorinated PCBs into low-chlorinated PCBs which can be more easily degraded by microorganisms. In this study, soil samples contaminated by PCBs were collected from an e-waste recycling site in Taizhou, Zhejiang Province. The remediation of combined nZVI and PCBs-degrading strain Rhodococcus pyridinovorans R04 was carried out to investigate the removal effect of PCBs in soil. The results showed that the combined treatment of nZVI and degrading strain R04 had better effects than the treatment of nZVI or R04 alone in removing PCBs or various chlorinated PCB congeners in soil. After combined treatment with nZVI and degrading strain R04 for 32 d, the removal rate of PCBs in soil reached 59.4%, which was higher than 46.1% of nZVI treatment and 34.4% of degrading strain R04 treatment (P＜0.05). Therefore, the combination of nZVI and degrading bacteria in the remediation of PCBs contaminated soil has good application potential.